Predictive value of prehypertension for metabolic syndrome, diabetes, and coronary heart disease among Turks - Onat, Altan; Yazici, Mehmet; Can, Guenay; Kaya, Zekeriya; Bulur, Serkan; Hergenc, Gulay (OXFORD UNIV PRESS, 2008)
BACKGROUND Predictors of prehypertension and the latter's significance in predicting metabolic syndrome (MetS), type 2 diabetes (DM), and incident coronary heart disease (CHD) need further exploration. METHODS Individuals with or without prehypertension (blood pressure (BP) 120-139 systolic or 80-89 mm Hg diastolic) were studied prospectively in a representative sample of Turkish adults. RESULTS Mean age of 1,501 men and 1,533 women was 48 12 years at baseline. Prehypertension, identified in 32.8% of the sample, differed from the normotensive group mainly by age-adjusted obesity measures and C-reactive protein (CRP) and progressed to hypertension at more than twofold annual incidence as normotension did. In logistic regression analysis, adjusted for sex, age, heart rate, and smoking status, prehypertension waspredictive for risk of MetS in both genders (relative risk (RR) 1.55 (95% confidence interval (CI) 1.21; 1.99)) compared with normotensives. However, DM and CHD were significantly predicted by prehypertension only in women (RR 2.06 and 1.98, respectively, for outcomes). Cardiometabolic risks in women were largely independent of obesity. Body mass index (BMI) at baseline predicted significantly subsequent development of new prehypertension in both genders (hazard ratio 1.39 (95% Cl 1.17; 1.65)) and CRP tended to contribute to this risk. CONCLUSIONS Prehypertension, compared with normotension, approximately doubles the risk for DM, MetS, and CHD in women without conferring substantial risk in Turkish men, except toward MetS. Excess cardiometabolic risk of prehypertension in women is independent of obesity. BMI is a determinant of prehypertension.
Keywords: JOINT NATIONAL COMMITTEE; CARDIOVASCULAR-DISEASE; INSULIN-RESISTANCE; INFLAMMATORY MARKERS; ABDOMINAL OBESITY; RISK-FACTOR; HYPERTENSION; PREVALENCE; MEN; DETERMINANTS; Cardiovascular System & Cardiology